2008
DOI: 10.1136/bjsm.2007.041400
|View full text |Cite
|
Sign up to set email alerts
|

Head, face and neck injury in youth rugby: incidence and risk factors

Abstract: Objectives: In this study, the incidence of head, neck and facial injuries in youth rugby was determined, and the associated risk factors were assessed. Design: Data were extracted from a cluster randomised controlled trial of headgear with the football teams as the unit of randomisation. No effect was observed for headgear use on injury rates, and the data were pooled. Setting: General school and club-based community competitive youth rugby in the 2002 and 2003 seasons. Participants: Young male rugby union fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(65 citation statements)
references
References 34 publications
(34 reference statements)
3
57
1
Order By: Relevance
“…In three of these studies the professional adult male neck injury rates ranged from 1.00 (CI: −0.77, 2.95) to 2.73 (CI: 0.89, 6.41)/1000 match playerhours. 28,39,42 Comparatively one semi-inclusive time-loss defined study 48 of male youths reported an injury rate of 3.3 (CI: 2.7, 4.0)/1000 match player-hours (Supplement 7). After consideration of injury rate confidence intervals there does not appear to be a difference in neck injury rate between professional men and male youth in studies which use a semi-inclusive time-loss sports injury definition.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…In three of these studies the professional adult male neck injury rates ranged from 1.00 (CI: −0.77, 2.95) to 2.73 (CI: 0.89, 6.41)/1000 match playerhours. 28,39,42 Comparatively one semi-inclusive time-loss defined study 48 of male youths reported an injury rate of 3.3 (CI: 2.7, 4.0)/1000 match player-hours (Supplement 7). After consideration of injury rate confidence intervals there does not appear to be a difference in neck injury rate between professional men and male youth in studies which use a semi-inclusive time-loss sports injury definition.…”
Section: Resultsmentioning
confidence: 99%
“…Four studies 28,39,42,48 utilised a semi-inclusive timeloss definition which allowed for meaningful comparison (Supplement 7). In three of these studies the professional adult male neck injury rates ranged from 1.00 (CI: −0.77, 2.95) to 2.73 (CI: 0.89, 6.41)/1000 match playerhours.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…1,12,[18][19][20]25,30,31,36,40 Measures to reduce the number of catastrophic injuries have included law changes and educational initiatives. 25,30,31 Laws governing the scrum, including scrum engagements, and the tackle have been adapted to make the game safer and to avoid non-fatal catastrophic injuries to the cervical spine.…”
Section: Introductionmentioning
confidence: 99%